Laestadius, Laestadianism and contemporary Sami and Tornedalian literature - Kaisa Maliniemi (Approaching Religion, 2020)
Review of Anne Heith's Laestadius and Laestadianism in the Contested Field of Cultural Heritage: A Study of Contemporary Sámi and Tornedalian Texts (Umeå University, 2018).